The epidemiology of food allergy in Europe: protocol for a systematic review - Nwaru, Bright I (BioMed Central, 2013)
BACKGROUND: The European Academy of Allergy and Clinical Immunology is in the process of developing its Guideline for Food Allergy and Anaphylaxis, and this protocol of a systematic review is one of seven inter-linked evidence syntheses that are being undertaken in order to provide a state-of-the-art synopsis of the current evidence base in relation to epidemiology, prevention, diagnosis and clinical management and impact on quality of life, which will be used to inform the formulation of clinical recommendations. The aims of the systematic review will be to understand and describe the epidemiology of food allergy, i.e. frequency, risk factors and outcomes of patients suffering from food allergy, and to describe how these characteristics vary by person, place and time. METHODS: A highly sensitive search strategy has been developed to retrieve articles that have investigated the various aspects of the epidemiology of food allergy. The search will be implemented by combining the concepts of food allergy and its epidemiology from electronic bibliographic databases. DISCUSSION: This systematic review will provide the most up to date estimates of the frequency of food allergy in Europe. We will attempt to break these down by age and geographical region in Europe. Our analysis will take into account the suitability of the study design and the respective study biases that could affect exposure and outcome. We will examine the different methods to diagnose food allergy and the associated measures of occurrence.